Wheat gluten and spray-dried plasma protein blends for nursery pigs - Burnham, L.L.; Kim, I.H.; Hines, Robert H.; Hancock, Joe D. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Using a 50:50 blend of spray-dried plasma protein (SDPP):spray-dried wheat gluten (WG) (i.e., with each as approximately 4% of the diet) gave the greatest ADG and ADFI, while reducing diet costs compared to the control diet (i.e., 8% SDPP). Even with a slight decrease in efficiency of gain, the marked decrease in diet cost will yield better cost of gain with a 50:50 blend versus using only SDPP.
Keywords: Swine; Nursery; Wheat gluten; Plasma protein